EVALUASI KUALITAS PELAYANAN PRIMA CARGO HANDLING TERHADAP KEPUASAN PELANGGAN PADA PT. GAPURA ANGKASA CABANG DENPASAR - RACHMA, SHANIA AULIA; KASIANI, KASIANI; KENCANAWATI, AA. AYU MIRAH; YUDISTIRA, COKORDA GEDE PUTRA; MARHENI, LILY; SARJANA, I MADE (Universitas Mahasaraswati K. Mataram, 2023)
This study aims to determine the quality of excellent service to cargo handling service officers at PT. Gapura Angkasa Denpasar Branch to find out the service attributes that require top priority in improvement in order to formulate a strategy for improvement. The population in this study was customer cargo of 2911 people, determining the sample size using the Slovin formula and obtained a sample of 96.7 rounded up to 97 people. The data analysis method used is descriptive statistics, Importance Performance Analysis (IPA), and Customer SatisfAction Index (CSI) with quantitative data types. The results of this study indicate that the quality of service is not entirely satisfactory with the value of the level of conformity 84%, the average value of performance and expectations of 3.92 and 4.67 then the value of the gap is -0.75 and the level of customer satisfAction with the services provided is 78.63% meaning quite satisfied. Service attributes that need improvement are the dimensions of Attitude (Attitude), Attention (Attention) and Appearance (Appearance). The formulated strategy includes, conducting training programs in accordance with standard operating procedures (SOP), implementing 3S procedures (Greetings, Smiles, and Greetings), a new service procedure was made in accordance with the company's standard operating procedures (SOP) and the company held training programs on excellent service quality in proper communication techniques. And provide socialization or counseling, especially about physical and non-physical Appearance, such as dressing, how to convey information in good words, and not offensive